PENENTUAN KUOTA BURU DAN INTRODUKSI POPULASI RUSA SAMBAR UNTUK MENJAMIN PERBURUAN LESTARI (Determining Hunting Quota and Population Introduced for Sustainable Hunting of Sambar Deer) - Agus Priyono Kartono; Yanto Santosa; Dudung Darusman; Achmad Machmud Thohari (Media Konservasi, 2008)
Hunting quota is the number of animals of hunting species destined to harvesting from the hunting population in the current year. Setting hunting quota is designed to ensure sustainable use of hunting game and conservation of ecosystem diversity. In the case that population of hunting species within hunting area is absence or not enough to ensure hunting activity, a number of animals must be introduced. The study showed that maximum sustained yield for hunting in the Masigit-Kareumbi Hunting Park was 674 individuals. Based on this quota, the individual number of animal should be introduced to hunting area as width as 12540,73 ha was 3.938 individuals that consist of 657 males and 3.281 females. Hunting season is after 5 years of population introduced.Keywords: hunting quota, sambar deer, conservation, maximum sustained yield, introduced population